PFT1, the MED25 subunit of the plant Mediator complex, promotes flowering through CONSTANS dependent and independent mechanisms in Arabidopsis - Iñigo, Sabrina (2012)
Two aspects of light are very important for plant development: the length of the light phase or photoperiod and the quality of incoming light. Photoperiod detection allows plants to anticipate the arrival of the next season, whereas light quality, mainly the red to far-red ratio (R:FR), is an early signal of competition by neighbouring plants. phyB represses flowering by antagonising CO at the transcriptional and post-translational levels. A low R:FR decreases active phyB and consequently increases active CO, which in turn activates the expression of FT, the plant florigen. Other phytochromes like phyD and phyE seem to have redundant roles with phyB. PFT1, the MED25 subunit of the plant Mediator complex, has been proposed to act in the light-quality pathway that regulates flowering time downstream of phyB. However, whether PFT1 signals through CO and its specific mechanism are unclear. Here we show that CO-dependent and -independent mechanisms operate downstream of phyB, phyD and phyE to promote flowering, and that PFT1 is equally able to promote flowering by modulating both CO-dependent and -independent pathways. Our data are consistent with the role of PFT1 as an activator of CO transcription, and also of FT transcription, in a CO-independent manner. Our transcriptome analysis is also consistent with CO and FT genes being the most important flowering targets of PFT1. Furthermore, comparison of the pft1 transcriptome with transcriptomes after fungal and herbivore attack strongly suggests that PFT1 acts as a hub, integrating a variety of interdependent environmental stimuli, including light quality and jasmonic acid-dependent defences.